Estuary Changes of Cipunagara and Cimanuk River Using Landsat Imagery Spatial Analysis - Wawan Hendriawan Nur; Marfasran Hendrizan; Ayu Utami Nurhidayati; Ahmad Fauzi Ismayanto (BULLETIN OF THE MARINE GEOLOGY, 2020)
The north coastal Java located in the West Java, especially in Cirebon, Indramayu, and Subang, occurs loss and forming new land by abrasion and accretion processes. Observation using satellite imagery can be used as an initial stage to determine the distribution of abrasion and accretion around the north coastal area. Observation of land changes was assigned using Landsat imagery from 1978 to 2020. The result shows that inland change was controlled by abrasion and accretion. It is occurred in Indramayu and Subang, especially in several areas around large rivers e.g. Cipunegara and Cimanuk Rivers. Estuary changes in the Cipunegara and Cimanuk Rivers were controlled by the high flux sediment deposition of the river mouths affecting the new land forming due to the accretion process. Monitoring through Landsat satellite imagery on the Cipunagara River from 1978 to 2020 shows that there was 205 Ha of new land. Remote sensing analysis in the Cimanuk River area shows that the estuary line from 1978 to 2020 experienced accretion or new land forming for 629 Ha.Keywords: North coastal Java, accretion, Landsat, river estuary analysis, Cipunegara River, Cimanuk RiverKawasan pantai utara Jawa di Jawa Barat, khususnya daerah Cirebon, Indramayu, dan Subang, memiliki permasalahan hilang atau terbentuknya daratan baru melalui proses abrasi dan akresi. Pengamatan mengunakan citra dapat dijadikan tahapan awal untuk mengetahui sebaran abrasi dan akresi di sekitar wilayah pantai utara. Observasi perubahan daratan dilakukan dengan menggunakan citra landsat tahun 1978 dan 2020. Hasilnya memperlihatkan bahwa telah terjadi perubahan daratan, baik proses abrasi maupun akresi, di beberapa wilayah di sekitar muara-muara sungai besar seperti Sungai Cipunegara dan Sungai Cimanuk. Perubahan muara Sungai Cipunegara dan Sungai Cimanuk lebih disebabkan oleh tingginya pengendapan sedimen pada muara sungai tersebut dan membentuk lahan baru karena proses akresi. Pemantauan melalui citra satelit di Sungai Cipunagara data citra tahun 1978 sampai 2020 memperlihatkan penambahan lahan baru sebanyak 205 H. Analisis remote sensing citra di wilayah Sungai Cimanuk terlihat garis muara pantai pada tahun 1978 hingga tahun 2020 mengalami akresi atau penambahan lahan baru 629 H.Kata Kunci: Pantai utara Jawa, akresi, Landsat, analisis muara sungai, Sungai Cipunegara, Sungai Cimanuk